2015
DOI: 10.22216/jit.2015.v9i1.39
|View full text |Cite
|
Sign up to set email alerts
|

Implikasi Corporate Governance terhadap Kinerja Family Business di Indonesia

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Family businesses that could embrace an entrepreneurial mindset might give SMEs a major increase for long-term success (Nugroho, 2016). In order to ensure the longevity of a family firm, family business governance is undoubtedly an excellent combination with an entrepreneurial spirit (Itan & Lestari, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Family businesses that could embrace an entrepreneurial mindset might give SMEs a major increase for long-term success (Nugroho, 2016). In order to ensure the longevity of a family firm, family business governance is undoubtedly an excellent combination with an entrepreneurial spirit (Itan & Lestari, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, the process of corporate governance appears to play a significant role in determining the success of a a family-business company that listed in stock exchange (Itan & Lestari, 2015). This understanding indicated that SMEs are aware that they must operate their businesses appropriately (Wardhana, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Some control variables are something that in the previous research was known to have an impact on firm value, namely 1) Firm Size measured by LogAsset, 2) Firm Age is the number of age of the company since its establishment, 3) Leverage measured by DER ratio, 4) TATO measured by dividing number of sales with total assets and 5) Current Ratio which is the result of dividing current assets with current liabilities (Afza & Nazir, 2014;Itan & Lestari, 2015;Ariff & Hashim, 2014;Huguet & Gandia, 2016;Appolos N. et al , 2016;Kristanti & Priyadi, 2016;Assidi et al, 2016;Ling & Wahab, 2018;Asiri & Hameed, 2014). Table 1 explains that the minimum firm value is 0.24 while the maximum value is 18.64.…”
Section: Variable and Measurementmentioning
confidence: 99%